Ensino de língua portuguesa no 9º ano do Ensino fundamental II: análise crítica na perspectiva da Eeducação linguística - Gonçalves, Gisley Aparecida (2013)
The Portuguese language teaching in the basic education II has been the subject of many debates among the governments, teachers, managers, and often, parents of students, because of the need of an education that aims the development of the communicative competences of the student opposed to a static and fragmented language teaching. Following these discussions, the analysis of the need comes up on how working with the mother tongue has been done in real situations inside the classroom facing a new profile of students and reality in the 21st century. This essay includes the Portuguese language teaching for the 9th grade in the basic education II, in a critical perspective of the Linguistic Education through a methodology of case study involving two public schools in the state of São Paulo, Brazil. Our study aims to analyze if the education given underlies the formation of the polyglot speakers in their own language (Bechara,1999), if the teachers do the transposition of knowledge, if they contemplate the several grammars in their classes and if they work the linguistic variation looking forward to the development of the communicative competence of the student. To do this research we used the analysis of official documents like LDB 9394/96 (a law that regulate the education in Brazil) and PCNs (National Curricular Parameters) in the Portuguese language, besides the Educational Political Projects, the annual plans of the involved teachers, the questions answered by the teachers and also the analysis of some classes. After the data analysis we noticed that even when we have the consciousness of the importance of the Portuguese language and of the learning objectives to native speakers and even knowing the theories that base a functional teaching of the language, the teachers still have difficulties in developing a distinguished work with the mother tongue that does not recur only in meta language, but that gives the sense to the text, the reflection about how the language works and that prioritize the language in use and the development of the communicative competence of the student to his/her insertion as a conscious citizenship in the society